MITIGASI SPRITUAL DALAM NASKAH LONTAR ROGA SANGHARA BHUMI - I Nyoman Suka Ardiyasa (Sanjiwani: Jurnal Filsafat, 2019)
The island of Bali is an island very vulnerable to disaster, it is proven with historical records that Bali has experienced a major earthquake better known as Gejer Bali. Various efforts have been made by the community from the past until now in the effort of mitigation done in sekala and niskala. In the community, people believe that if they want to avoid the disaster then the community must implement the tri hita karana, while niskala (theologically) done with various upakara. Upakara sources and the types of disasters that occur in this world are believed to be contained in the Lontar Roga Sanghara Bhumi manuscript. But the existence of the manuscript is not much to know so it is necessary to conduct a more in-depth review so that it can be disseminated to the public. To focus on these reviews, we focused on three problem formulas: analyzing the summary of the Roga Sanghara Bhumi lontar manuscripts, the types of disasters mentioned in the Roga Sanghara Bhumi lontar, and the theological attempts made in dealing with the disasters mentioned in lontar Roga Sanghara Bhumi. From the results of the study conducted it is briefly known that the lontar Roga Sanghara Bhumi contains about the causes of catastrophe or disaster occurred in the world, the types of catastrophes or disasters that can occur in the world and some characteristics of the coming disaster or disaster, while the types The disaster mentioned in the lontar of Roga Sanghara Bhumi is a type of disaster that repeats every sasih it and the kind of disaster that occurs which is seen from the bad gesture, in the concept of Lontar Roga Sanghara Bhumi called Durmanggala. The theological efforts undertaken in tackling the disasters mentioned in the lontar of Roga Sanghara Bhumi are performing ceremonies that are shown to Ida Sang Hyang Widhi Wasa with the aim of pleading for salvation such as Prayascita Ceremony, Master Piduka, Labuh Gentuh, Jagat, Pamahayu Bumi and Nangluk Mrana. All these ceremonies are theological (mitigation) efforts in reducing disaster risks that occur on earth.